Influence of gallopamil on the gastric effects of stress in conscious rats - ÇORAK, AHMET; KURTEL, HIZIR; ÇETİNEL, ŞULE; ALİCAN, YAŞAR İNCİ (KARGER, 1996)
The influence of the calcium-channel blocker gallopamil on cold-restraint stress (CRS)-induced gastric effects was investigated in conscious rats with gastric cannula. CRS, while leading to multiple gastric lesions, reduced gastric acid output and mast cell count, but increased the gastric emptying rate of acid solutions, Intraperitoneally injected gallopamil (1 mg/kg), given Ih before CRS administration, prevented gastric lesion formation and partially reversed mast cell count and the emptying of acid solutions, but had no further effect on acid output, However, gallopamil in unrestrained rats did not significantly affect acid emptying or mast cell count, Regarding calcium involvement in the pathophysiology of stress-induced gastric lesions, the possible antiulcer actions of gallopamil involved in the prevention of CRS-induced lesion formation may be attributed to its putative stabilizing effect on mast cells and gastric emptying.
Keywords: gallopamil; gastric emptying; cold-restraint stress; mast cells; gastric acid secretion; ulcer; ACID-SECRETION; COLD RESTRAINT; MAST-CELLS; CHOLECYSTOKININ; INHIBITION; VERAPAMIL; ULCERATION; MOTILITY; SULFATE; ULCERS